Clinical Characteristics and Risk Factors Associated With Acute Kidney Injury Inpatient With Exertional Heatstroke: An Over 10-Year Intensive Care Survey - Wu, Ming; Wang, Conglin; Liu, Zheying; Zhong, Li; Yu, Baojun; Cheng, Biao; Liu, Zhifeng (Frontiers in Medicine, 2021)
Background: Exertional heat stroke (EHS) is a life-threatening injury that can lead to acute kidney injury (AKI). The clinical characteristics of and risk factors for EHS complicated with AKI have been poorly documented. Methods: A retrospective study with EHS admitted to the intensive care unit (ICU) from January 2008 to June 2019 was performed. Data including baseline clinical information at admission, main organ dysfunction, 90-day mortality and total cost of hospitalization were collected. Results: A total of 187 patients were finally included, of which 82 (43.9%) had AKI. AKI patients had more severe organ injury and higher total hospitalization costs than non-AKI patients. Multivariate logistic analysis showed that lymphocyte, neutrophil, D-dimer and myoglobin (MB) ≥ 1,000 ng/ml were independent risk factors for AKI caused by EHS. In addition, SOFA score [hazard ratio (HR) 4.1, 95% confidence interval (95% CI) 1.6–10.8, P = 0.004] and GCS score (HR 3.2, 95% CI 1.2–8.4 P = 0.017) were the risk factor for 90-day mortality in patients with EHS complicated with AKI, with an area under the curve (AUC) of 0.920 (95% CI 0.842–0.998, P < 0.001) and 0.851 (95% CI 0.739–0.962, P < 0.001), respectively. Survival analysis showed that the 90-day mortality in AKI patients was significantly high (P < 0.0001) and the mortality rate of patients with AKI stage 2 was the highest than other stages. Conclusions: EHS complicated with AKI is associated with higher hospitalization costs and poorly clinical outcomes. MB ≥1,000 ng/ml, Inflammation, coagulation were associated with the occurrence and development of AKI. Early treatment strategies based reducing the SOFA and GCS score may be pivotal for improving the prognosis of EHS.